2020
DOI: 10.4314/gmj.v54i4s.6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 patients admitted at the Korle-Bu Teaching Hospital, Accra, Ghana

Abstract: Design: Study design was a retrospective single-center review of hospital data.Setting: The study was conducted at the COVID-19 Treatment Center of the Department of Medicine and Therapeutics of the Korle-Bu Teaching hospital in Accra, Ghana.Participants and study tools: A total of fifty patients with laboratory (rRT-PCR) confirmed COVID-19 infection were involved in the study. A chart review of the medical records of the patients was conducted and the data obtained was documented using a data extraction form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…This study showed that the presence of comorbidity and clinical symptoms have a direct association with disease status, as reported in several studies in Ghana [16,17]. The majority of the patients showed symptoms (64%), predominantly with cough, headache, general weakness, fever, and sore throat, among others; this is a finding similar to other studies [17,18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study showed that the presence of comorbidity and clinical symptoms have a direct association with disease status, as reported in several studies in Ghana [16,17]. The majority of the patients showed symptoms (64%), predominantly with cough, headache, general weakness, fever, and sore throat, among others; this is a finding similar to other studies [17,18].…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that the presence of comorbidity and clinical symptoms have a direct association with disease status, as reported in several studies in Ghana [16,17]. The majority of the patients showed symptoms (64%), predominantly with cough, headache, general weakness, fever, and sore throat, among others; this is a finding similar to other studies [17,18]. It has been reported by Adjei et al (2020) that fever is the third commonest symptom seen in COVID-19 patients in Greater Accra (Ghana); however, in our study in Kumasi (Ghana), it was the fourth most common symptom.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Older adults with one or two comorbidities have a higher risk of being infected with COVID-19 and experiencing episodes of mortality (10)(11)(12). A preliminary study conducted on COVID-19 patients in Ghana showed that people with the most common underlying illnesses, such as hypertension, diabetes, asthma, heart disease, and chronic kidney disease were diagnosed with COVID-19 (13). This places older adults, particularly those suffering from diabetes and hypertension, at a higher risk for severe illness from COVID-19 (14), resulting in an increase in stress, depression, and isolation during the peak of COVID-19 (2).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 treatment has a wide spectrum because the disease varies from self-limiting to life-threatening cases. 2 3 4 Therefore, the current COVID-19 treatment guidelines classify patients according to severity and recommend appropriate treatment for each patient. 5 Patients with mild illness are defined as individuals who have any symptoms of COVID-19 but who do not show evidence of lower respiratory disease, and patients with moderate illness show signs and symptoms of lower respiratory disease and SpO2 ≥ 94% on room air at sea level.…”
Section: Introductionmentioning
confidence: 99%